2015
DOI: 10.1007/s00223-015-0042-1
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Effects of Advanced Glycation End Products (Ages) in Bone Matrix on Osteoclastic Resorption

Abstract: Advanced glycation end products (AGEs) accumulate in bone extracellular matrix as people age. Previous studies have shown controversial results regarding the role of in situ AGEs accumulation in osteoclastic resorption. To address this issue, this study cultured human osteoclast cells directly on human cadaveric bone slices from different age groups (young and elderly) to warrant its relevance to in vivo conditions. The cell culture was terminated on the 3rd, 7th, and 10th day, respectively, to assess temporal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Here, our study rst observed that M1 macrophages prefer to highly express the above osteoclast-related markers, proving that M1 macrophages have greater osteoclastogenesis potential, which is consistent with the research of Huang et al [27]. To date, some reports have been put to con rm that AGEs are related to osteoclasts metabolism, but its speci c role in regulating bone resorption is not clear [28,29]. We then examined the role of AGEs in the differentiation of M1 macrophages into osteoclasts.…”
Section: Discussionsupporting
confidence: 90%
“…Here, our study rst observed that M1 macrophages prefer to highly express the above osteoclast-related markers, proving that M1 macrophages have greater osteoclastogenesis potential, which is consistent with the research of Huang et al [27]. To date, some reports have been put to con rm that AGEs are related to osteoclasts metabolism, but its speci c role in regulating bone resorption is not clear [28,29]. We then examined the role of AGEs in the differentiation of M1 macrophages into osteoclasts.…”
Section: Discussionsupporting
confidence: 90%
“…65 Nevertheless, reactive oxygen species may induce cell apoptosis and damage to DNA and structural components of cells and matrix. 66,67 Increased mitochondrial generation of reactive oxygen species has been linked to greater periodontitis in diabetics. 68 Diabetic patients have an increased number of inducible nitric oxide synthase-positive cells in the periodontium and levels of lipid peroxides are elevated in the gingival crevicular fluid of type 2 diabetes mellitus patients.…”
Section: Iab E Te S Peri Odontal D Is E a S E S And Infl Ammamentioning
confidence: 99%
“…However, this hypothesis has been recently challenged . Nevertheless, reactive oxygen species may induce cell apoptosis and damage to DNA and structural components of cells and matrix . Increased mitochondrial generation of reactive oxygen species has been linked to greater periodontitis in diabetics .…”
Section: Diabetes Periodontal Diseases and Inflammationmentioning
confidence: 99%
“…Patients with T2D have higher levels of AGEs due to hyperglycemia, which can also increase the production of inflammatory cytokines and reactive oxygen species, setting off a vicious cycle of chronic inflammation and bone resorption ( 59 ). Activating of RAGE in both osteoclasts ( 60 , 61 ) and osteoblasts ( 46 , 62 ) could induce up-regulation of pro-inflammatory cytokines such as IL-1β, IL-6, and TNF-α, which could directly affect bone homeostasis ( 63 , 64 ). Accumulating evidence indicates that the TGF-β also plays an important role in the osteogenic progress affected by AGEs, especially biologically potent AGE2 and AGE3 ( 65 , 66 ).…”
Section: Discussionmentioning
confidence: 99%